Explaining the Failure of Environmental Law in China - Xu, Guangdong; Faure, Michael (Columbia Journal of Asian Law, 2016)
China has experienced remarkable economic growth in recent decades, with an average annual growth of approximately ten percent. As a result of this unprecedented and miraculous growth, China’s economy has expanded impressively and is now the second largest economy in the world (with a nominal GDP of USD 10.36 trillion in 2014), behind only the United States. China is currently the world’s largest exporter, largest manufacturer, largest holder of foreign exchange reserves, and second-largest destination of foreign direct investment (FDI). China’s growth miracle, however, has not arrived without costs. Environmental pollution is another serious challenge faced by the Chinese government and society. In response to the increasing pressures caused by its deteriorating environmental conditions, the Chinese government has adopted a series of strategies in recent years to begin to pay the environmental debt that has been ignored for decades. However, the effects of these efforts have been modest at best, and the environmental quality in China has not been improved sufficiently to meet public health and safety requirements. Certain institutional weaknesses, such as legislative vagueness, lack of resources and governmental support for enforcement, local protectionism and restricted public participation, have all been identified in the current literature as being responsible for the ineffectiveness of China’s environmental governance. We will show that economic growth has inexorably become an overriding objective that derives from the Party’s desperation to maintain power because increased wealth accumulation supports the regime by appeasing the people, co-opting powerful elites, and strengthening the security apparatus. Environmental protection is not vital to the Party’s survival and therefore is sacrificed for economic growth, at least until pollution-related unrest endangers the Party. Section II offers a brief overview of China’s environmental problems, with special attention to both air pollution and water pollution. Section III discusses the failure of China’s environmental governance institutions, including its courts and regulatory agencies, in addressing environmental challenges. Section IV analyses how China’s political system—its authoritarian nature, its legitimacy-pursuing efforts, and its decentralized power structure in particular—have contributed and continue to contribute to the current environmental disaster. Section V concludes.